Organizational reflections of the relationship between artificial ıntelligence and emotional ıntelligence in the context of phenomenology and Cartesian dualism - Yaroglu, Aslihan Canbul (EMERALD GROUP PUBLISHING LTD, 2025)
PurposeThe purpose of this article is to deepen understanding of how emotional intelligence (EI) and artificial intelligence (AI) affect organizational behavior from a phenomenological perspective. Through philosophical lenses - particularly Descartes, Husserl and Merleau-Ponty - it highlights the contrasts and similarities between these forms of intelligence. The study aims to explore how AI and EI shape human experience and meaning-making in organizations, providing insights into how AI integration can foster more human-centered organizational practices.Design/methodology/approachThis study employs a phenomenological approach to explore the philosophical underpinnings of EI and AI. By examining Descartes' Cartesian dualism and Husserl's phenomenology, the study analyzes the alignment and divergence between AI and these philosophical perspectives. The methodology integrates literature review and conceptual analysis to link philosophical insights with their organizational behavior implications, offering a framework that critically examines AI's impact on human experience and organizational dynamics.FindingsThe findings highlight that emotional intelligence, rooted in the body-mind interaction, offers a human-centered view of experience, distinct from artificial intelligence. However, combining AI with EI can enhance organizational behavior by promoting more empathetic approaches. While AI can mimic cognitive functions, it lacks the embodied emotional experiences essential for human interaction. This insight emphasizes the need for AI systems to support, rather than disrupt, organizational meaning-making processes.Originality/valueThis article offers an original interdisciplinary perspective, merging phenomenological philosophy with organizational behavior. By examining emotional and artificial intelligence through Descartes, Husserl and Merleau-Ponty, the study presents fresh insights into AI design that prioritizes human-centered development. It contributes to AI ethics and organizational behavior literature by emphasizing the role of emotional intelligence in guiding AI integration within organizational contexts.
Keywords: Phenomenology; Artificial Intelligence; Husserl; Merleau Ponty; Descartes; Cartesian Dualism; Emotional intelligence; INTELLIGENCE; MANAGEMENT; CHALLENGES; VALIDITY; UTILITY; ISSUES; Business & Economics